The care taker’s discourse about taking care of the elderly with alzheimer’s disease - Aline Miranda Fonseca; Enedina Soares (Rev Rene)
The aim of this research is to learn about the intervenient factors that contribute with the diffi culties felt by the care taker in the activities developed by the elderly with Alzheimer’s disease. The sceneries chosen for this study were support groups of care takers and relatives of elderly people with Alzheimer’s disease or similar dementia. Eight care takers who attended support groups participated in this study. The obtained data were qualitatively analyzed at the light of Lefêvre and his recommended principles, about the Collective Subject Discourse. The diffi culties found by the care taker could be outlined in three aspects: care subjectiveness; family and care; and corporal hygiene. We found out that the groups which supported the family and the care takers of the elderly Alzheimer’s disease carriers are rich knowledge fi elds that deserve attention and participation of the health professionals, mainly nurses.